Delayed immune-related events (DIRE) after discontinuation of immunotherapy: diagnostic hazard of autoimmunity at a distance. Issue 1 (3rd July 2019) - Couey, Marcus A.; Bell, R. Bryan; Patel, Ashish A.; Romba, Meghan C.; Crittenden, Marka R.; Curti, Brendan D.; Urba, Walter J.; Leidner, Rom S.
Abstract : Background: The risk of delayed autoimmunity occurring months or years after discontinuation of immunotherapy is frequently asserted in the literature. However, specific cases were rarely described until 2018, when a wave of reports surfaced. With expanding I-O indications in the adjuvant/neoadjuvant curative setting, growing numbers of patients will receive limited courses of immunotherapy before entering routine surveillance. In this context, under-recognition of DIRE could pose a growing clinical hazard. Methods: The aim of this study was to characterize DIRE through identification of existing reports of delayed post-treatment irAE in cancer patients treated with immunotherapy. We performed a PubMed literature review from 2008 through 2018 to determine the median data safety reporting window from existing I-O clinical trials, which we then applied to define the DIRE cutoff, and collated all qualifying reports over the same time span. DIRE was defined as new immune-related adverse events (irAE) manifesting ≥90 days after discontinuation of immunotherapy. Results: Median duration of I-O clinical trials data safety reporting was 90 days (82% ≤ 90 days). DIRE cutoff was thus set as ≥90 days post-immunotherapy. We identified 23 qualifying cases; 21 by literature review and 2 from our institution. Median off-treatment interval to DIRE was 6 months (range: 3 to 28). Median cumulative immunotherapy exposure was 4 doses (range: 3 to 42). Involvement included endocrine, neurologic, GI, pulmonary, cardiac, rheumatologic and dermatologic irAE. Conclusions: As immunotherapy indications expand into the curative setting, often with brief exposure and potentially sequenced with multimodality treatments, it will be necessary to recognize an emerging diagnostic complex, which we have termed delayed immune-related events (DIRE). Clinical vigilance has the potential to reduce morbidity from diagnostic delay, as irAE are generally manageable with prompt initiation of treatment – or from misdiagnosis - as misattribution can lead to unnecessary or harmful interventions as we describe. DIRE should therefore figure prominently in the differential diagnosis of patients presenting with illnesses of unclear etiology, irrespective of intervening treatments or interval post-immunotherapy, both of which can confound diagnosis. Increased recognition will rest on delineation of DIRE as a clinical diagnostic entity.